Resource partitioning between Microlophus occipitalis and Stenocercus puyango (Sauria: Tropiduridae) in Cerros de Amotape National Park, Tumbes, Peru - Guzmán, Alfredo (2021)
Activity, microhabitat use, and diet are patterns commonly used to define the saurian community structure, because of differential exploitation allowing coexistence at the same time and place. We analyze resource partitioning between two sympatric saurian species, Stenocercus puyango and Microlophus occipitalis, in the transitional area of the Pacific Tropical Forest and the Dry Forest inside Cerros de Amotape National Park (PNCA) in Tumbes, northwestern of Peru. Microlophus occipitalis and S. puyango both showed a unimodal activity pattern with higher activity around 13:00 h, with a mean body temperature of 34.83 °C and 32.17 °C respectively, observing a significant relationship between body and environmental (air and substrate) temperatures. Rocks and tree trunks were the most frequent microhabitats used by M. occipitalis while S. puyango were registered more frequently over leaf litter. The diets of both tropidurids were composed by arthropods, ants, and insect larvae mainly. Similarities in activity times (temporal niche) and diet (trophic niche) should be related to phylogenetic relationship and environmental characteristics of PNCA (seasonality, vegetal composition) meanwhile differences in space use and microhabitat thermal quality will be related to thermal quality in the area.